A BIT OF GUILLAUME APOLLINAIRE'S POETICS: “THE HORSE”, “ZONE” AND THE CALLIGRAM OF THE HORSE - Martins, Maria (Revista de Letras, 2023)
The work presents proposals for the translation of three poems by the French poet of the early 20th century, Guillaume Apollinaire. In the comments, I explore the notions of rhythm, the subject of the poem and modernity in the line of thought of the French linguist, poet and translator Henri Meschonnic. Also, in line with this thought, I draw attention to how the components of Ethics, Poetics and Politics present themselves in the poems inside a process of reciprocal interaction. These are poems published in 1911, 1913 and 1918. They have differentiated rhythmic and poetic proposals, which involve different challenges to the translator. The three poems already have translations into the Portuguese language. Thus, my proposals imply revisitation, presupposing that they imply a different look at rhythm, understood in a very comprehensive way since it does not discard the metric but is not reduced to it.